(untitled) (Journal of the College of Basic Education, 2023)
Meaning is one of the problems which seems difficult to deal with to such extent that Leonard Bloomfield, who resisted the mentalist approach to language, considered it impossible to define meaning till we have a scientifically accurate knowledge of everything in the speaker’s world. Linguists consider meaning as one of the most complex subjects to deal with and some of them are in doubt whether meaning can be studied objectively and systematically as phonology and grammar or not. The complexity and vagueness of semantics are due to the fact that semantics is not concerned with one specific field but with various fields such as: philosophy, logic, psychology, anthropology, and sociology. Many linguists, recently, do their new theory of grammar. This paper is intended to present a brief study of the status of semantics in Transformational generative grammar. It is of three parts: Part One is concerned with the scope of semantics. Part Two presents a historical survey of semantics and its historical development in the schools of grammar. Part Three is a review of the status of semantics in the Transformational schools of grammar.